Mixed-methods development of a new patient-reported outcome instrument for chronic low back pain: part 2—The Patient Assessment for Low Back Pain–Impacts (PAL-I) - Bushnell, Donald M. (Pain, 2018)
We describe qualitative and quantitative development and preliminary validation of the Patient Assessment for Low Back Pain–Impacts (PAL-I), a patient-reported outcome measure for use in chronic low back pain (cLBP) clinical trials. Concept elicitation and cognitive interviews (qualitative methods) were used to identify and refine symptom concepts. Classical test theory and Rasch measurement theory (quantitative methods) were used to evaluate item-level and scale-level performance of the PAL-I using an iterative approach between qualitative and quantitative methods. Patients with cLBP participated in concept elicitation interviews (N = 43), cognitive interviews (N = 38), and assessment of paper-to-electronic format equivalence (N = 8). A web-based sample of self-reported patients with cLBP participated in quantitative studies to evaluate preliminary (N = 598) and revised (n = 401) drafts and patients with physician-diagnosed cLBP (N = 45) participated in preliminary validation of the PAL-I. The instrument contained 9 items describing cLBP impacts (walking, sitting, standing, lifting, sleep, social activities, travelling, climbing, and body movements). Item-level performance, scale structure, and scoring seemed to be appropriate. One-week test–retest reproducibility was acceptable (intraclass correlation coefficient 0.88 [95% confidence interval, 0.78-0.94]). Convergent validity was demonstrated with PAL-I total score and Roland-Morris Disability Questionnaire (Pearson correlation 0.82), MOS-36 Physical Functioning (−0.71), and MOS-36 Bodily Pain (−0.71). Individual item scores and total score discriminated between numeric rating scale tertile groups and painDETECT categories. Interpretation of paper and electronic administration modes was equivalent. The PAL-I demonstrated content validity and is potentially useful to assess treatment benefit in clinical trials of cLBP therapies.